Optimizing hospital-to-home transitions for older persons in rural communities: a participatory, multimethod study protocol - Mary T. Fox; Souraya Sidani; Jeffrey I. Butler; Mark W. Skinner; Marilyn Macdonald; Evelyne Durocher; Kathleen F. Hunter; Adrian Wagg; Lori E. Weeks; Ann MacLeod; Sherry Dahlke (Implementation Science Communications, 2021)
Abstract Background Transitional care involves time-limited interventions focusing on the continuity of care from hospital to home, to optimize patient functioning and management. Providing interventions, as part of transitional care, that optimize the functioning of older people with dementia is critical due to the small window of opportunity in which they can return to their baseline levels of functioning. Yet prior research on transitional care has not included interventions focused on functioning and did not target older people with dementia in rural communities, limiting the applicability of transitional care to this population. Accordingly, the goal of this study is to align hospital-to-home transitional care with the function-related needs of older people with dementia and their family-caregivers in rural communities. Methods In this multimethod study, two phases of activities are planned in rural Ontario and Nova Scotia. In phase I, a purposive sample of 15–20 people with dementia and 15–20 family-caregivers in each province will rate the acceptability of six evidence-based interventions and participate in semi-structured interviews to explore the interventions’ acceptability and, where relevant, how to improve their acceptability. Acceptable interventions will be further examined in phase II, in which a purposive sample of healthcare providers, stratified by employment location (hospital vs. homecare) and role (clinician vs. decision-maker), will (1) rate the acceptability of the interventions and (2) participate in semi-structured focus group discussions on the facilitators and barriers to delivering the interventions, and suggestions to enable their incorporation into rural transitional care. Two to three focus groups per stratum (8–10 healthcare providers per focus group) will be held for a total of 8–12 focus groups per province. Data analysis will involve qualitative content analysis of interview and focus group discussions and descriptive statistics of intervention acceptability ratings. Discussion Findings will (1) include a set of acceptable interventions for rural transitional care that promote older patients’ functioning and family-caregivers’ ability to support patients’ functioning, (2) identify resources needed to incorporate the interventions into rural transitional care, and (3) provide high-quality evidence to inform new transitional care practices and policies and guide future research.